2014
DOI: 10.15226/2374-6882/1/2/00110
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Endocardial Radial Strain in Hypertensive Patients with Electrocardiographic Strain Pattern on Twodimensional Speckle-Tracking Echocardiography

Abstract: Background: Strain ST-T changes on Electrocardiography (ECG) is a well-recognized marker of the presence and severity of Left Ventricular (LV) hypertrophy, which is usually associated with subendocardial dysfunction. However, the relationship between ST-T change and subendocardial dysfunction in hypertensive patients is unknown. Recently, two-dimensional speckle-tracking echocardiography has been used to define myocardial deformation parameters of the LV segment. Herein, we assessed subendocardial dysfunction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…This indicates that myocardial SR is more sensitive than LV EF and seems to be suitable to detect early stages of LV dysfunction. 27 Furthermore, Morris et al 28 and Ohara et al 29 reported using systolic LV strain assessed by 2D-STE that there was subtle LV systolic dysfunction in patients with HTN, even though LV EF was normal. We obtained a similar finding, as there was no difference in LV EF among the five groups, whereas not only LV strain in longitudinal and radial directions but also SR during systole in three directions assessed by novel 3D-STE even in hypertensive patients with concentric remodeling was already reduced.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that myocardial SR is more sensitive than LV EF and seems to be suitable to detect early stages of LV dysfunction. 27 Furthermore, Morris et al 28 and Ohara et al 29 reported using systolic LV strain assessed by 2D-STE that there was subtle LV systolic dysfunction in patients with HTN, even though LV EF was normal. We obtained a similar finding, as there was no difference in LV EF among the five groups, whereas not only LV strain in longitudinal and radial directions but also SR during systole in three directions assessed by novel 3D-STE even in hypertensive patients with concentric remodeling was already reduced.…”
Section: Discussionmentioning
confidence: 99%